Maternal dietary patterns and depressive symptoms during pregnancy: The Born in Guangzhou Cohort Study. Issue 5 (May 2021) - Huang, Peiyuan; Wei, Dongmei; Xiao, Wanqing; Yuan, Mingyang; Chen, Niannian; Wei, Xueling; Xie, Junyi; Lu, Jinhua; Xia, Xiaoyan; Lu, Minshan; Shen, Songying; He, Jianrong; et al.
Summary: Background & aims: Maternal depression has been reported to be harmful to maternal and child health, and nutrition-mental health interactions may play a key role, but evidence from longitudinal studies throughout pregnancy remains insufficient. This study aimed to investigate the association of maternal dietary patterns with depressive symptoms throughout pregnancy. Methods: This study was based in the Born in Guangzhou Cohort Study. Dietary patterns were defined by cluster analysis based on validated food frequency questionnaires in mid-pregnancy. A healthy diet score was also developed based on predefined criteria of existing dietary guidelines. Depressive symptoms were measured by Self-rating Depression Scale (SDS) in both early and late pregnancy, with SDS scores ≥53 defined as having depressive symptoms. Associations of dietary patterns with SDS scores were examined by linear-mixed models; associations of dietary patterns with the odds of having depressive symptoms were examined by mixed-effects logistic models. The associations of the healthy diet score with both dietary patterns and depressive symptoms were also explored. Results: Six dietary patterns were identified in 17, 430 pregnant women, namely 'Varied' (n = 3902, 22.4%), 'Vegetables' (n = 3269, 18.8%), 'Meats' (n = 2951, 16.9%), 'Cereals' (n = 2719, 15.6%), 'Milk' (n = 2377, 13.6%), and 'Fruits' (n = 2212, 12.7%). There were 19.3% and 15.7% of participants with depressive symptoms in early and late pregnancy, respectively. Compared with the 'Varied' pattern, all other patterns were associated with lower SDS scores during pregnancy except for 'Cereals' ('Vegetables': adjusted β [aβ] −0.78, 95% CI −1.16,  −0.40; 'Meats': aβ −0.48, 95% CI −0.87,  −0.09; 'Milk': aβ −0.52, 95% CI −0.94,  −0.10; 'Fruits': aβ −0.85, 95% CI −1.27,  −0.42). The 'Vegetables' (adjusted OR [aOR] 0.79, 95% CI 0.67, 0.93), 'Milk' (aOR 0.76, 95% CI 0.63, 0.91), and 'Fruits' (aOR 0.77, 95% CI 0.64, 0.93) patterns were associated with lower odds of having depressive symptoms during pregnancy than the 'Varied' pattern. Results for the healthy diet score revealed the healthiness of the 'Vegetables', 'Fruits', and 'Milk' patterns and supported an inverse association between healthy dietary patterns and depressive symptoms throughout pregnancy. Conclusions: Diets rich in vegetables, fruits, nuts, and dairy products had an inverse association with depressive symptoms throughout pregnancy. Our findings add support to the existing dietary guidelines that healthy diets might also have potential benefits to maternal mental health.